Extracellular loops matter – subcellular location and function of the lysine transporter Lyp1 from Saccharomyces cerevisiae. (11th March 2020) - van't Klooster, Joury S.; Bianchi, Frans; Doorn, Ruben B.; Lorenzon, Mirco; Lusseveld, Jarnick H.; Punter, Christiaan M.; Poolman, Bert
Abstract : Yeast amino acid transporters of the APC superfamily are responsible for the proton motive force‐driven uptake of amino acids into the cell, which for most secondary transporters is a reversible process. The l ‐lysine proton symporter Lyp1 of Saccharomyces cerevisiae is special in that the Michaelis constant from out‐to‐in transport ( K m out → in ) is much lower than K m in → out, which allows accumulation of l ‐lysine to submolar concentration. It has been proposed that high intracellular lysine is part of the antioxidant mechanism of the cell. The molecular basis for the unique kinetic properties of Lyp1 is unknown. We compared the sequence of Lyp1 with APC para‐ and orthologues and find structural features that set Lyp1 apart, including differences in extracellular loop regions. We screened the extracellular loops by alanine mutagenesis and determined Lyp1 localization and activity and find positions that affect either the localization or activity of Lyp1. Half of the affected mutants are located in the extension of extracellular loop 3 or in a predicted α‐helix in extracellular loop 4. Our data indicate that extracellular loops not only connect the transmembrane helices but also serve functionally important roles. Abstract : We performed alanine‐scanning mutagenesis of the extracellular loops of the yeast lysine transporter Lyp1. We find positions that affect either the localization or activity of Lyp1. Half of the affected mutants are located in the extension of extracellular loop 3 or in a predicted α‐helix in extracellular loop 4. We conclude that extracellular loops of amino acid transporters of the APC superfamily serve functionally important roles.